SPEED OPTIMIZATION IN CHILDREN AGED 14 TO 15, WHO PRACTICE THE FOOTBALL GAME (GYMNASIUM, 2009)
The experiment consisted in elaborating and applying a set of means for the speed development, inthe experiment group, between June 15th 2007 and June 15th 2008. More precisely, at the training sessionsperformed during this period, in the group of children aged 14 to 15, at the “Pajura” SSC no. 1, an interval of15 to 20 minutes/ workout was allotted to the general and specific speed development. It is to mention thatthe means used by us were correlated with the period we were in (the preparatory, pre-competition,competition and transition periods).In the control group, the number of training sessions and their duration were almost identical with those inthe experiment group, but, in this latter, the speed development wasn’t given a particular attention, by keeping to theinitial schedule proposed by the coach. Generally, the experimental application of the speed training methodology tochildren aged 14-15, who practice the football game, through a set of means conceived for the speed education,determined the obtaining of an increased efficiency of the experimental actions.